Accountability and Transparency of Mosque Financial Reporting Based on ISAK 35: A Case Study of Mosque in Surabaya - Maya Ayu Aisyah; Luluk Hanifah (Varied Knowledge Journal, 2026)
This study aims to analyze the accountability and transparency of the financial management of Al-Falah Mosque in Surabaya based on ISAK 35 as the financial reporting standard for non-profit entities. The study employed a qualitative descriptive approach using primary data obtained through interviews with the mosque management and secondary data in the form of the Al-Falah Mosque’s 2023 financial statements. Data were analyzed using the Miles and Huberman qualitative analysis model, which includes data reduction, data display, and conclusion drawing and verification. The findings indicate that Al-Falah Mosque has implemented most of the provisions of ISAK 35 through the preparation of a statement of financial position, statement of activities, statement of changes in net assets, and statement of cash flows. Accountability is demonstrated through the implementation of Standard Operating Procedures (SOPs), internal supervision, annual financial reporting, and evaluation based on reward and punishment mechanisms. Transparency is reflected in the open disclosure of information to the public, deliberative decision-making processes, and the accessibility of financial documents. The implementation of accountability and transparency principles has enhanced public trust in the mosque’s financial management, encouraging greater community participation and support for its programs. Nevertheless, improvements are still needed in separating the statement of activities from the statement of changes in net assets and in complying with fund reporting requirements under ISAK 35. This study confirms that the implementation of ISAK 35 contributes to improving the quality of financial reporting, strengthening governance, and fostering public trust in religious institutions.